2023
DOI: 10.1042/bst20220014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics in macrophages: divide to conquer or unite to survive?

Abstract: Mitochondria have long been appreciated as the metabolic hub of cells. Emerging evidence also posits these organelles as hubs for innate immune signalling and activation, particularly in macrophages. Macrophages are front-line cellular defenders against endogenous and exogenous threats in mammals. These cells use an array of receptors and downstream signalling molecules to respond to a diverse range of stimuli, with mitochondrial biology implicated in many of these responses. Mitochondria have the capacity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 167 publications
0
5
0
Order By: Relevance
“…Mitochondrial fission has primarily been associated with proinflammatory responses and metabolic adaptation, so it can be considered combative strategy immune cells utilize. In contrast, mitochondrial fusion has a more protective role in limiting cell death under conditions of nutrient starvation (57). Alterations in mitochondrial dynamics are associated with cancer development, and progression of cardiovascular and neurodegenerative conditions (58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial fission has primarily been associated with proinflammatory responses and metabolic adaptation, so it can be considered combative strategy immune cells utilize. In contrast, mitochondrial fusion has a more protective role in limiting cell death under conditions of nutrient starvation (57). Alterations in mitochondrial dynamics are associated with cancer development, and progression of cardiovascular and neurodegenerative conditions (58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria can alter their distribution within the cell, as well as undergo fission and fusion (52,82). Work in peripheral macrophages demonstrates that such mitochondrial structural remodeling can regulate key cellular functions (3439). We found that microglial mitochondria exhibit most of the same forms of dynamic remodeling described in other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in neurons, mitochondria can regulate emergence of synaptic plasticity (45,75) and, in astrocytes, mitochondria can regulate morphological and functional maturation of the cell (75,77). Mitochondria can also regulate the inflammatory state of macrophages and capacity of these cells to rapidly adjust their cellular phenotype in response to various challenges (34)(35)(36)(37)(38)(39)76). Given evidence that mitochondrial dysfunction is implicated in developmental delays, epilepsy, migraine, psychiatric disorders, aging, and risk for neurodegeneration (78,79), a better understanding of how mitochondria impact the function of specific CNS cell types should be a priority for the field.…”
Section: The Underappreciated Complexity Of Mitochondriamentioning
confidence: 99%
See 2 more Smart Citations